Vertical Proportion of the Face: A Cephalometric study (Orthodontic Journal of Nepal, 2021)
Introduction: Balance in vertical facial proportion is an important criteria for good esthetics. Variations in vertical growth are common and have certain orthodontic implications. The objectives of this study were to determine mean upper anterior facial height and lower anterior facial height, ratio between UAFH to LAFH and their difference among genders in skeletal Class I patients with different vertical growth pattern among patients visiting department of Orthodontic and Dentofacial orthopedics, Tribhuvan University Dental Teaching Hospital, Kathmandu.Materials and Method: This study was descriptive observational cross sectional study with 105 sample aged from 18-25 years. Pretreatment cephalometric radiograph of Skeletal Class I patients were taken and divided into three growth patterns as group I (normal growth pattern), group II (horizontal growth pattern ) and group III (vertical growth pattern ). Upper anterior facial height (N-ANS) and lower anterior facial height (ANS-Me) of all samples were measured on lateral cephalogram with cephalometric tracing ruler parallel to true vertical line. Descriptive statistics was used to calculate mean, minimum, and maximum values standard deviations with p value